The Effect of Educational Attainment and Gender Inequality on Unemployment Rates and Economic Resilience - Pramandyah Fitah Kusuma; Trie Hierdawati; Abdal Ahmed (International Forum of Researchers and Lecturers, 2024)
This study examines the relationship between educational attainment, gender inequality in education, and their impact on unemployment rates and economic resilience across various regions. Gender inequality in education has long-term consequences on labor market outcomes and economic stability. In regions with higher gender inequality, the underutilization of female talent results in higher unemployment rates and weaker economic resilience. In contrast, regions with higher gender equality in education show improved labor market performance and a more resilient economy. The study utilizes cross-regional regression analysis, incorporating data on education levels, gender inequality indices, unemployment rates, and economic resilience metrics. The findings suggest that gender inequality in education plays a more significant role in shaping unemployment rates and economic resilience than traditional macroeconomic variables such as GDP and inflation. Furthermore, the results highlight the importance of improving access to education for underrepresented genders, particularly women, to foster more inclusive and sustainable economic growth. The study emphasizes the need for policies that promote gender equality in education as a means to enhance labor market outcomes and strengthen economic resilience. Limitations of the study include potential data constraints and regional variations in cultural, economic, and policy contexts, which may affect the generalizability of the findings. Future research could expand this study by exploring different regions and countries to gain a deeper understanding of the long-term effects of reducing gender inequality in education on economic outcomes.